Analysis of textural properties in cheese incorporated with antioxidant rich berries. - Guiné, Raquel (2017)
This work intended to evaluate the textural properties in fresh cheeses made with incorporation of red fruits (blueberry and raspberry) because of the importance that this type of properties carries for deﬁning the organoleptic quality of the product and, consequently, determine consumer acceptance. The fresh cheeses were made following the usual processing steps but somewhere on the process, some fruits were added, whole or grinded in the middle of the cheese mass. To evaluate the textural characteristics, two types of tests were carried out using a Texture Analyser, a compression test and a puncture test. It was concluded that the addition of fruits into fresh cheese produces important changes in the textural properties, namely diminishing hardness and chewiness and at the same time increasing resilience. Also the external and internal ﬁrmness vary, increasing in both cases as compared to the control sample. Regarding adhesiveness, it was found not meaningful for the compression test but very signiﬁcant for the puncture test, as a result of the type of contact between the probe and the chees in each case.